Tubular Colonic Duplication Presenting as Rectovestibular Fistula - Karkera, Parag J. (Pediatr Gastroenterol Hepatol Nutr, 2015)
Complete colonic duplication is a very rare congenital anomaly that may have different presentations according to its location and size. Complete colonic duplication can occur in about 15% of all gastrointestinal duplications. Double termination of tubular colonic duplication in the perineum is even more uncommon. We present a case of a Y-shaped tubular colonic duplication which presented with a rectovestibular fistula and a normal anus. Radiological evaluation and initial exploration for sigmoidostomy revealed duplicated colons with a common vascular supply. Endorectal mucosal resection of theduplicated distal segment till the colostomy site with division of the septum of the proximal segment and colostomy closure proved curative without compromise of the continence mechanism. Tubular colonic duplication should always be ruled out when a diagnosis of perineal canal is considered in cases of vestibular fistula alongwith a normal anus.